2011
DOI: 10.1111/j.1365-2419.2011.00574.x
|View full text |Cite
|
Sign up to set email alerts
|

Climate change in the southeastern Bering Sea: impacts on pollock stocks and implications for the oscillating control hypothesis

Abstract: Concern about impacts of climate change in the Bering Sea prompted several research programs to elucidate mechanistic links between climate and ecosystem responses. Following a detailed literature review, Hunt et al. (2011) (Deep-Sea Res. II, 49, 2002) developed a conceptual framework, the Oscillating Control Hypothesis (OCH), linking climaterelated changes in physical oceanographic conditions to stock recruitment using walleye pollock (Theragra chalcogramma) as a model. The OCH conceptual model treats zooplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
175
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(181 citation statements)
references
References 52 publications
5
175
0
1
Order By: Relevance
“…Variance in total zooplankton abundance does not seem to tell the whole story, and some more detailed hypotheses therefore involve the occurrence of qualitative and phenological changes in the food source (Beaugrand et al 2003, Möllmann et al 2003, van der Lingen et al 2006. Climate-induced alterations of the local copepod communities have been reported in both temperate and Arctic regions (Planque & Taylor 1998, Möllmann et al 2003, Beaugrand 2004, Helaouët & Beaugrand 2009, Coyle et al 2011, Kjellerup et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Variance in total zooplankton abundance does not seem to tell the whole story, and some more detailed hypotheses therefore involve the occurrence of qualitative and phenological changes in the food source (Beaugrand et al 2003, Möllmann et al 2003, van der Lingen et al 2006. Climate-induced alterations of the local copepod communities have been reported in both temperate and Arctic regions (Planque & Taylor 1998, Möllmann et al 2003, Beaugrand 2004, Helaouët & Beaugrand 2009, Coyle et al 2011, Kjellerup et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…After retrieval of the bongo nets, all fish larvae were removed from the cod ends, and a volume displacement measurement of remaining zooplankton (including small gelatinous zooplankton; large jellyfish were removed so as not to bias the displacement volume) was taken as a coarse measure of zooplankton wet weight biomass and an index of overall production at each station , Coyle et al 2008, 2011. All samples were preserved at sea in 5% buffered formalin seawater solution.…”
Section: Methodsmentioning
confidence: 99%
“…Companion studies in Icy Strait also indicated that food quantity can be more important than food quality for growth and survival of juvenile salmon (Weitkamp and Sturdevant 2008). As a result, monitoring the composition, abundance, and timing of zooplankton taxa with diff erent life-history strategies may permit the detection of climate-related changes in the seasonality and interannual abundance of prey fi elds (Park et al 2004;Coyle et al 2011;). In contrast, "top-down" predation events can also aff ect salmon year-class strength by piscivorous fi sh .…”
Section: Discussionmentioning
confidence: 99%